Comparative study on competitive status of China, the USA and Russia before the Beijing Olympics - Jing, L. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. II, 2008)
Introduction The 2008 Beijing Olympics are approaching, and more and more people are beginning to foresee the outcomes of results especially for China, the USA and Russia. This paper will objectively make a comparative study on competitive status of China, the USA and Russia through the winning outcomes of the three countries over the past four years. Methods The methods used include literature review, investigation and logic analysis. Results / Discussion China won 32 gold medals and took 2nd place on the gold medal count at the Athens Olympics, but the medal numbers and athletes in the first eight fell behind the USA and Russia by far, which indicates the competitive sport of the USA and Russia have more potential and thus the two countries can potentially gain more medals. As a whole, the primary opponents of China in the Beijing Olympics are still the USA and Russia. The superiority of these nations in track and field and swimming is obvious. The disparity in track and field and swimming between China and the two countries has become greater and greater in the past four years. China`s superiority project, including table tennis, badminton, diving, women's weightlifting, and female Tae Kwon Do, saw China claim 17 gold medals (out of a total of 23), which represents 74% of the gold-medals gained at the last Olympics. Whilst China dominated these events in the previous games, development since is questionable. In summary, there is still a great disparity in competitive status between China, the USA and Russia. The USA`s gold medal winning position cannot be changed in the Beijing Olympics. Who will take second place in the Beijing Olympics? China or Russia? This will completely depend on the performances of the athletes of the two countries. There is no doubt that China, the USA and Russia will take the first three places in the gold medal count in the Beijing Olympics.